DIETARY DIVERSITY AND ASSOCIATED FACTORS AMONG WOMEN OF REPRODUCTIVE AGE IN PHILIPPINES - Akhyudi, Dewi Muthia Charissa; Qurniyawati, Eny; Tama, Tika Dwi; Astutik, Erni (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Dietary diversity is the main key to preventing various nutritional problems in women of reproductive age. The study aimed to assess dietary diversity and associated factors among women of reproductive age in the Philippines. This study is a cross-sectional study based on data from the 2022 Philippines National Demographic Health Survey (NDHS) with a total weighted sample of 25,315 women aged 15-49 years and who are not pregnant. The statistical analysis used was the chi-square test and logistic regression with a 95% CI. Overall, 70,8% of women aged 15-49 years achieved dietary diversity. Women with age 35-49 years [aPR = 2,20; 95%CI: 1,96-2,46], relatively rich for economic status [aPR = 1,23; 95%CI: 1,07-1,40], who access of mass media [aPR = 1,51; 95%CI: 1,38-1,65], didn’t consumed unhealthy foods [aPR = 0,43; 95%CI: 0,39-0,48] and didn’t consumed any sweet beverages [aPR = 0,77; 95%CI: 0,65-0,92] had a statistically significant with the acceptable dietary diversity among women of reproductive age in Philippines. To increase the adequate level of dietary diversity in women of productive age, interventions related to strengthening nutritional health promotion and its dissemination through mass media and socio-economic support from the relevant government are indeed too.